(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2020)
Blockchain Based Applications are becoming increasingly popular in the Government Sector due to increased needs of Trust and Transparency. Due to its Decentralized architecture, strong encryption algorithms and immutable timestamping it is being used in diverse applications including Health Care, Education, Voting and Smart Governance. Blockchain has many variants based on Ownership, Consensus Protocols and Tokenization Strategy. This paper analyses Blockchain Taxonomy based on Ownership and Access rights. It then reviews a multitude of Blockchain based Government applications based on their Ownership characteristics and needs for anonymity and Read as well as Write privileges. Based on the classification framework, the final objective is to create and verify the Blockchain Framework Mapping based on the Applications Business and Security requirements.